2006
DOI: 10.1093/mutage/gel049
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage induced by Ochratoxin A in the HK-2 human kidney cell line: evidence of the relationship with cytotoxicity

Abstract: Ochratoxin A (OTA) is a mycotoxin produced by species of the genera Aspergillus and Penicillium. The kidneys are the target organ of this mycotoxin and it is considered a potent renal carcinogen in male rats. The mechanisms of its genotoxicity and carcinogenicity have been studied thoroughly, but controversial results have been published. The aim of this study was to evaluate the ability of OTA to produce single-strand DNA breaks and oxidative DNA damage in the human renal proximal tubular epithelial cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 48 publications
8
56
0
1
Order By: Relevance
“…OTA mechanisms of action are not clearly determined but the ability to generate reactive oxygen species (ROS) may explain the lipid, protein and DNA damage (Ringot et al, 2006). The test battery for evaluating OTA genotoxicity gave negative results (IARC, 1993), but some positive results are found in some in vitro and in vivo studies such as DNA breaks in mammalian cell lines (Ehrlich et al, 2002;Lebrun and Follmann, 2002;Arbillaga et al, 2007), DNA damage and micronuclei in primary cultures of human and rat kidney cells (Robbiano et al, 2004) and cytogenetic damage and DNA adducts in rats treated with OTA (Mally et al, 2005;Pfohl-Leszkowicz and Manderville, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…OTA mechanisms of action are not clearly determined but the ability to generate reactive oxygen species (ROS) may explain the lipid, protein and DNA damage (Ringot et al, 2006). The test battery for evaluating OTA genotoxicity gave negative results (IARC, 1993), but some positive results are found in some in vitro and in vivo studies such as DNA breaks in mammalian cell lines (Ehrlich et al, 2002;Lebrun and Follmann, 2002;Arbillaga et al, 2007), DNA damage and micronuclei in primary cultures of human and rat kidney cells (Robbiano et al, 2004) and cytogenetic damage and DNA adducts in rats treated with OTA (Mally et al, 2005;Pfohl-Leszkowicz and Manderville, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Based on findings of OTA-related DNA adducts in cell cultures as well as in animal and human kidneys, some authors support the notion of direct OTA genotoxic action after metabolic activation (Pfohl-Leskowicz & Manderville, 2007). However, some studies indicate that OTA is not able to form reactive intermediates capable of interacting with DNA (Mally et al, 2005), and it has been suggested that OTA can induce DNA damage through oxidative stress (Arbillaga, Azqueta, Ezpeleta, & Lopez de Cerain, 2007;Domijan, Želježić , Kopjar, & Peraica, 2006;Kamp, Eisenbrand, Schlatter, Würth, & Janzowski, 2005;Liu et al, 2012). Similarly, some authors have proposed that oxidative stress may be the underlying mechanism of FB 1 genotoxicity Mary, Theumer, Arias, & Rubinstein, 2012;Mobio et al, 2000Mobio et al, , 2003, while others have failed to find an increase in ROS production together with DNA damage after FB 1 exposure, suggesting oxidative stress is not involved in FB 1 -induced DNA damage (Galvano et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism that leads to OTA genotoxicity, as measured through the comet assay, is not fully understood, evidence from in vitro (with different cell types) and in vivo studies suggests the role of oxidative stress (Ali et al, 2014;Arbillaga et al, 2007;Aydin et al, 2014;Hadjeba-Medjdoub et al, 2012;Hibi et al, 2013aHibi et al, , 2013bLebrun and Föllmann, 2002;Yang et al, 2014). It has also been reported that OTA biotransformation produces metabolites that are more genotoxic than the original toxin.…”
Section: Discussionmentioning
confidence: 99%